System at the Regional Financial Management Agency (BPKD) of Langsa City - Esti Alemia Puspita (Yayasan Putra Adi Dharma, 2024)
Cash management becomes an important aspect in local government administration, as it maintains financial balance and efficiency in the implementation of governmental activities. Cash comprises cash on hand and bank balance that can be utilized to finance governmental activities. The cash receipt system encompasses various sources such as taxes, levies, and receivables. Meanwhile, the cash disbursement system includes various transactions such as purchasing goods and paying debts. Both systems must be accurately recorded and deposited, as well as well-managed to prevent misappropriation and ensure compliance with established procedures. The implementation of computerized systems such as SIMDA can help accelerate and enhance efficiency in cash receipt and disbursement in local government administration.